ANALISIS DAMPAK PERTUMBUHAN EKONOMI TERHADAP TERBUKANYA KESEMPATAN KERJA DI KOTA PONTIANAK - Jonathan Giovanni; Mochammad Faisal Fadli (STIE 'INDONESIA' Pontianak, 2020)
The study was based on data released by BPS Pontianak which results showed that there was an increase in the Pontianak Regional Gross Domestic Product (PDRB) in 2017 based on a 2010 constant price of 5.05%. Another fact found is that economic growth is able to encourage an increase in the number of new companies in 2017 by 1,349 (one thousand three hundred forty-nine) new businesses. Based on these facts the author is interested in examining more deeply whether the economic growth that occurred in the city of Pontianak is able to encourage the availability of employment for residents of the workforce both who are still in the process of looking for work and who are already working. Data obtained through questionnaires that were distributed to the informants who were scattered in all districts in the city of Pontianak which will then be analyzed. Questionnaire data will then be compared with data released by Pontianak City BPS on economic and unemployment levels. This research is a basic study in which the measurement of the level of technological readiness is at level 1, which in turn will be an illustration for the real conditions in Pontianak in terms of opportunities to find work and will be input for related parties in determining the steps that need to be taken to expand employment opportunities in the city of Pontianak.